Lowering Blood Pressure With β‐Blockers in Combination With Other Renin‐Angiotensin System Blockers in Patients With Hypertension and Type 2 Diabetes: Results From the GEMINI Trial - Wright, Jackson T. (J Clin Hypertens (Greenwich), 2007)
The effects of β‐blockade in addition to more specific renin‐angiotensin system (RAS) blockers on blood pressure (BP) in patients with diabetes are described. After washout of medications other than angiotensin‐converting enzyme inhibitors and angiotensin receptor blockers, patients were titrated to a BP level <130/80 mm Hg using therapy with carvedilol 6.25 to 25 mg bid (n=498) or metoprolol tartrate 50 to 200 mg bid (n=737). At the end of the β‐blocker titration period, a BP level <130/80 mm Hg was achieved in 37% of carvedilol‐treated and 36% of metoprolol‐treated participants who continued to receive a renin‐angiotensin system blocker. In the approximately 60% of participants in whom a BP level <130/80 mm Hg was not attained with renin‐angiotensin system blockade plus β‐blockade, hydrochlorothiazide was added in 43% and 44% of carvedilol and metoprolol groups, respectively; 25% (both arms) also required a calcium channel blocker. Among those in whom goal BP was not achieved, 42% of carvedilol‐ and 40% of metoprolol‐treated participants were not titrated to the highest dose of β‐blocker. The use of carvedilol compared with metoprolol did not effect glycemic control.